GUT MICROBIOTA AND ITS EFFECTS ON METABOLIC AND NEUROLOGICAL HEALTH - Pinheiro, Bruna Santana Silva; Rodrigues, Julia Gonçalves; Hildebrand, Letícia Beretta; Pacheco, Helen Fernanda Marcelino; Lopes, Beatriz Gabiatti; Dias, Fernanda Carolina Ribeiro; Paiva, Aline Dias; Gomes, Marcos de Lucca Moreira (Acta Biologica Brasiliensia, 2023)
The human gut microbiota plays various essential roles, including protection against pathogens, intestinal function regulation, synthesis of compounds for the host, diet compound metabolism, and direct influence on host homeostasis. The composition of the microbiota is influenced by factors like diet, age, and lifestyle, with the Westernized culture being associated with harmful imbalances. Disruption of the gut microbiota has been linked to various pathological processes, from intestinal syndromes to systemic conditions like allergies, insulin resistance, and neurological alterations. Microbiota disturbances can lead to cellular changes in colorectal tissue due to metabolic, genomic, and inflammatory influences. Therapeutic interventions to modulate the gut microbiota are considered promising approaches for managing and preventing these diseases. Continuous research on the gut microbiota and its relation to human health is of utmost importance to understand the underlying mechanisms and develop specific therapeutic interventions, complementing conventional treatment approaches.